(untitled) (RPG学研究: Japanese Journal of Analog Role-Playing Game Studies, 2024)
In contemporary Japan, many children with developmental disabilities attend after-school daycare services (referred to as "Afterschool Day Services," or ADS). As the needs of these children and their parents continue to grow, there is potential for table-top role-playing games (TRPGs) to serve as an effective support tool in such settings. This study conducted a brainstorming session with six staff members (including childcare workers and children's instructors) employed at an ADS center that consistently offers TRPG activities. Using the KJ method (affinity diagramming), the participants' narratives were analyzed and organized. The findings revealed a prominent focus on communication skills, with numerous key phrases relating to interaction with others being identified. This suggests that TRPGs could be recognized as valuable tools for supporting communication. Additionally, the participants noted that ADS centers are well-suited environments for implementing TRPG activities. These results indicate the potential for utilizing TRPGs in ADS settings, highlighting the need for further development of TRPG-based practices in the future.